2005
DOI: 10.1007/s00228-005-0938-1
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism of CYP2D6, CYP2C19, CYP2C9 and CYP2C8 in the Faroese population

Abstract: Objective: The purpose of the study was to study the distribution of poor and extensive metabolizers of CYP2C19 and CYP2D6 and to genotype for CYP2C8 and CYP2C9 among 312 randomly selected Faroese. Methods and Results:The participants were phenotyped for CYP2D6 with the use of sparteine. The distribution of the sparteine metabolic ratio (sparteine/didehydrosparteines) was bimodal, and 14.5% (n=44) (95% CI 10.7-18.9%) of the subjects were phenotyped as poor metabolizers. The frequency of poor metabolizers was h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
37
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 36 publications
8
37
3
Order By: Relevance
“…Calculated allele frequencies did not differ much from those reported earlier by other studies for Caucasians, as shown in Table 2. 17,18 Incidence of GVHD No statistic differences were found in the incidence of acute GVHD grade 2-4 for EMs, IMs and PMs with 28.2, 32.8 and 25%, respectively. The genotype of donors also had no significant influence on the incidence of GVHD grade 2-4 in patients.…”
Section: Frequency Of Ems Ims and Pmsmentioning
confidence: 97%
“…Calculated allele frequencies did not differ much from those reported earlier by other studies for Caucasians, as shown in Table 2. 17,18 Incidence of GVHD No statistic differences were found in the incidence of acute GVHD grade 2-4 for EMs, IMs and PMs with 28.2, 32.8 and 25%, respectively. The genotype of donors also had no significant influence on the incidence of GVHD grade 2-4 in patients.…”
Section: Frequency Of Ems Ims and Pmsmentioning
confidence: 97%
“…In European populations, the allele frequency of CYP2C8*3 ranges from 0.069 in Faroe Islanders to 0.198 in a Portuguese population, with an apparent north-to-south cline from lower to higher frequencies (Fig. 6;Yasar et al, 2002;Halling et al, 2005;Cavaco et al, 2006;Speed et al, 2009;1000Genomes Project Consortium, 2012Pechandova et al, 2012;Suarez-Kurtz et al, 2012). The allele is also quite common in European American and North American Hispanic populations, with frequencies of 0.09 and 0.08, respectively (Martis et al, 2013).…”
Section: A Population Geneticsmentioning
confidence: 99%
“…Introduction: The CYP2D6 polymorphism is an important determinant of TCA metabolism, and 7-10% of Europeans are CYP2D6 poor metabolizers (PM) (Alvan et al, 1990). We have recently shown an increased occurrence of CYP2D6 PMs (15%) in the Faroese population (Halling et al, 2005). Amitriptyline (AT) is the most widely used TCA.…”
Section: P 086 the Influence Of A Serotonin Transporter Polymorphism mentioning
confidence: 99%
“…Sparteine and metabolites were assayed by gas chromatography . CYP2D6*3, *4, *6 and *9 genotype analyses were performed by real-time polymerase chain reaction before using the Taqman technology (Halling et al, 2005) Plasma concentrations of AT and metabolites were determined by HPLC (Nielsen et al, 1993) and investigated in relation to CYP2D6 activity. Results: Of the 23 patients, five (22 % [95% CI: 7.5-43.7%]) were phenotyped and genotyped as CYP2D6 poor metabolizers (PMs).…”
Section: P 086 the Influence Of A Serotonin Transporter Polymorphism mentioning
confidence: 99%
See 1 more Smart Citation